Harapan dan Tantangan Entrepreneur di Kota Palu - Sukmawati Saleh; Munir Salham; Nurhayati Mansyur (Institute of Indonesia Arts and Culture (ISBI) Bandung, 2018)
ABSTRACT This paper begins with the phenomenon of the development of Young Entrepreneurs in the City of Palu which continues to develop both in terms of the number and type of business involved. The development of technology, easily accessible information flows and adequate infrastructure are supporting factors for the growth of the creative economy which is fronted by Entrepreneurs, espe-cially in Palu City. In the midst of the development of the creative economy, the hopes of young En-trepreneurs are tucked into building and advancing their efforts and challenges. Especially now that more and more competition and technology has become increasingly sophisticated, therefore as an Entrepreneur, it is required to try to create and innovate and also to be creative in doing everything so that our business continues to run smoothly as expected and desired. Keywords: Expectations, Challenges, Entrepreneurs and Young Entrepreneurs ABSTRAK Tulisan ini bermula dengan fenomena berkembangnya Entrepreneur Muda di Kota Palu yang terus mengalami perkembangan baik dari segi jumlah maupun jenis bisnis yang digeluti. Perkem-bangan teknologi, arus infomasi yang mudah diakses serta infrastruktur yang memadai merupakan faktor penunjang tumbuhnya ekonomi kreatif yang digawangi oleh para Entrepreneur khususnya di Kota Palu. Di tengah perkembangan ekonomi kreatif, terselip harapan para Entrepreneur muda da-lam membangun dan memajukan usaha mereka serta tantangan. Apalagi sekarang ini makin banyaknya persaingan dan teknologi sudah semakin canggih, maka dari itu sebagai wirausaha dituntut harus berusaha menciptakan dan berinovasi dan juga harus kreatif dalam melakukan segala hal agar usaha kita tetap berjalan lancar sesuai yang diharapkan dan diinginkan. Kata Kunci: Harapan, Tantangan, Entrepreneur dan Entrepreneur Muda